2015
DOI: 10.4012/dmj.2014-328
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of bone cement that fully transforms to carbonate apatite

Abstract: The objective of this study was to fabricate a type of bone cement that could fully transform to carbonate apatite (CO3Ap) in physiological conditions. A combination of calcium carbonate (CaCO3) and dicalcium phosphate anhydrous was chosen as the powder phase and mixed with one of three kinds of sodium phosphate solutions: NaH2PO4, Na2HPO4, or Na3PO4. The cement that fully transformed to CO3Ap was fabricated using vaterite, instead of calcite, as a CaCO3 source. Their stability in aqueous solutions was differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 29 publications
0
44
0
Order By: Relevance
“…In a dissolution-precipitation reaction, precipitation cannot occur without prior dissolution of the starting materials. The dissolution of starting materials is accelerated in acidic conditions, as mentioned by Cahyanto et al [21]. In other words, the dissolution of materials was slower in an alkaline solution.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In a dissolution-precipitation reaction, precipitation cannot occur without prior dissolution of the starting materials. The dissolution of starting materials is accelerated in acidic conditions, as mentioned by Cahyanto et al [21]. In other words, the dissolution of materials was slower in an alkaline solution.…”
Section: Resultsmentioning
confidence: 87%
“…2k. Cahyanto et al [21] reported that the crystals will interlock to set and harden. Although slightly different mechanical properties were reported, there were no differences in term of scaffolds' porosity treated in either NaHCO 3 or Na 2 CO 3 aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…For a core material, calcium carbonate (CaCO 3 ) was used to decrease the material resorption rate and promote the osteogenic potential due to Ca 2+ release. CO 3 Ap blocks are fabricated through a dissolution‐precipitation reaction using a precursor such as CaCO 3 , tricalcium phosphate, gypsum, and calcium phosphate dihydrate (Ayukawa, Suzuki, Tsuru, Koyano, & Ishikawa, ; Cahyanto, Maruta, Tsuru, Matsuya, & Ishikawa, ; Kunio Ishikawa, ; Kunio Ishikawa et al, ; Kanazawa et al, ; Lin, Matsuya, Nakagawa, Terada, & Ishikawa, ; Wakae et al, ). For example, CO 3 Ap blocks are fabricated by immersing a CaCO 3 block in the Na 2 HPO 4 solution.…”
Section: Introductionmentioning
confidence: 99%
“…2 Bone cement formulations consist of vaterite (a polymorph of CaCO 3 ) and dicalcium phosphate anhydrous (DCPA) as powder phase mixed with sodium phosphate solution can fully transform to CO 3 Ap in physiological conditions. 3,4,5 Based on the previous study, this CO 3 Ap cement with L/P ratio of 0.45 will set in 11 minutes. 3,4,5 The powder formulation is 40 wt% of vaterite and 60 wt% of DCPA were required for the full formation of CO 3 Ap.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,5 Based on the previous study, this CO 3 Ap cement with L/P ratio of 0.45 will set in 11 minutes. 3,4,5 The powder formulation is 40 wt% of vaterite and 60 wt% of DCPA were required for the full formation of CO 3 Ap. 3,4,5 Apatite cement can be used to repair bone defects such as alveolar bone defect and dental implant fixation.…”
Section: Introductionmentioning
confidence: 99%